A new genus and species of Brychiopontiidae Humes, 1974 (Crustacea: Copepoda:Siphonostomatoida) associated with an abyssal holothurian in the NortheastPacific nodule province - Mahatma, Radith; Arbizu, Pedro Martínez; Ivanenko, Viatcheslav N. (Zootaxa, 2008)
A new genus and species Neobrychiopontius galeronae gen. nov. sp. nov. is described based on female specimens from the Pacific nodule province associated with the abyssal holothurian Oneirophanta cfr. setigera (Ludwig, 1894) (Elasipodida, Deimatidae). The holothurian and copepods were collected at a depth of 4978 m during the cruise “Nodinaut” (Ifremer, 17 May – 28 June 2004) on RV Atalante using a spade corer operated from the submersible Nautile. The new genus has retained a greater number of plesiomorphic characters, when compared to its closest relative the monotypic genus Brychiopontius Humes, 1974 from the abyssal zone of the North Atlantic: proximal 3 segments of antennule articulates (fused in Brychiopontius), well developed mandibular palp and inner lobe of maxilla (both absent in Brychiopontius). On the other hand the new genus has only 2 outer spines on the third exopodal segment of leg 1 (instead of 3 in Brychiopontius). Two plesiomorphic characters hitherto unknown for the order Siphonostomatoida are present in the new genus viz. the inner lobe of the first segment of the maxilla is armed with 2 setae and the first segment of the mandibular palp is armed with 1 seta. Neobrychiopontius galeronae gen. et sp. nov. is the second species of Siphonostomatoida found in association with abyssal holothurians (both belonging to the genus Oneirophanta) and represents the first record of the family Brychiopontiidae in the Pacific Ocean.